Protection of Patient Data Confidentiality in Telemedicine Services In In-donesia: A Human Rights Perspective - Ari Rama, Bagus Gede; Sawitri Nandari, Ni Putu; Mahadewi, Kadek Julia (LEGAL BRIEF, 2025)
The growth of telemedicine in Indonesia has become an innovative solution to improve access to health services, especially in remote areas, but accompanied by an increased risk of leakage of sensitive patient data. This problem is exacerbated by the uneven implementation of data protection regulations, despite the implementation of the Personal Data Protection Law (PDP Law) of 2022, Minister of Health Regulation No. 20 of 2019, and provisions in the Health Law. This study uses a normative legal approach with analysis of legal documents, legal literature, and a study of secondary data related to data leakage incidents in the telemedicine sector. The discussion focused on reviewing the legal provisions that regulate explicit approval, transparency, and information security systems in the management of medical data, as well as analyzing the application of these norms in the field. Furthermore, this study integrates legal theories such as informational self-determination and contextual integrity, as carried out by leading experts (Warren & Brandeis, Solove, Westin, Nissenbaum, and Kuner), to assess the impact of data leaks on human rights, especially the right to privacy and protection of personal information. The results show that although regulations have been legally enforced, implementation constraints such as inequality in digital infrastructure, differences in legal interpretation at the local level, and cross-sector coordination are still major obstacles. Therefore, synergy between strict regulation and a multidisciplinary approach is urgently needed to ensure that telemedicine innovation goes hand in hand with full respect for human rights.